Re-placing Memory: Latter-day Saint Use of Historical Monuments and Narrative in the Early Twentieth Century - Flake, Kathleen (Religion and American culture, 2003)
In the winter of 1905, leaders of The Church of Jesus Christ of Latter-day Saints (L.D.S. or the “Mormons”) departed Utah on two, seemingly disparate, missions to the east coast. One contingent went to defend their church at Senate hearings in Washington, D.C.; the other, to Vermont to dedicate a monument to church founder Joseph Smith. These forays into national politics and religious memory re-fashioned Latter-day Saint identity, as well as public perception of Mormonism, for the remainder of the twentieth Century They also illuminate one of the quotidian mysteries of religion: how it adapts to the demands of time yet maintains its sense of mediating the eternal. It is axiomatic that religious communities are not exempt from the human condition; they must adapt to their temporal circumstances or die. What is not as often recognized is that churches bring a particular burden to this task because they offer their believers the hope of transcending time.